ALA Inhibits ABA-induced Stomatal Closure via Reducing H2O2 and Ca2+ Levels in Guard Cells - An, Yuyan; Liu, Longbo; Chen, Linghui; Wang, Liangju (Frontiers in Plant Science, 2016)
5-Aminolevulinic acid (ALA), a newly proved natural plant growth regulator, is well known to improve plant photosynthesis under both normal and stressful conditions. However, its underlying mechanism remains largely unknown. Stomatal closure is one of the major limiting factors for photosynthesis and absicisic acid (ABA) is the most important hormone in provoking stomatal closing. Here, we showed that ALA significantly inhibited ABA-induced stomatal closure using wild-type and ALA-overproducing transgenic Arabidopsis (YHem1). We found that ALA decreased ABA-induced H2O2 and cytosolic Ca2+ accumulation in guard cells with stomatal bioassay, laser-scanning confocal microscopy and pharmacological methods. The inhibitory effect of ALA on ABA-induced stomatal closure was similar to that of AsA (an important reducing substrate for H2O2 removal), CAT (a H2O2-scavenging enzyme), DPI (an inhibitor of the H2O2-generating NADPH oxidase), EGTA (a Ca-chelating agent) and AlCl3 (an inhibitor of calcium channel). Furthermore, ALA inhibited exogenous H2O2- or Ca2+-induced stomatal closure. Taken together, we conclude that ALA inhibits ABA-induced stomatal closure via reducing H2O2, probably by scavenging, and Ca2+ levels in guard cells. Moreover, the inhibitive effect of ALA on ABA-induced stomatal closure was further confirmed in the whole plant. Finally, we demonstrated that ALA inhibits stomatal closing, but significantly improves plant drought tolerance. Our results provide valuable information for the promotion of plant production and development of a sustainable low-carbon society.